Multistage artificial immune system for static VAR compensator planning - S. C. Mohd Nasir; M. H. Mansor; I Musirin; M. M Othman; T. M Kuan; K. Kamil; M. N Abdullah (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Interconnected network of transmission and distribution lines lead to losses in the system and weakening the voltage stability in the system. Installing Static VAR Compensator (SVC) in power system has known to improve the system by minimizing the total loss and improve the voltage profile of the system. This paper presents the application of Multistage Artificial Immune System (MAIS) technique to determine optimal size of SVC. The performance of this technique is tested on the IEEE 14-Bus Reliability Test System (RTS). The optimization results show that the proposed Multistage Artificial Immune System (MAIS) technique gives better solution of SVC compensator planning problem compared to single stage Artificial Immune System (AIS) in terms of lower total system loss and improved minimum voltage magnitude.